IMPLEMENTASI RODA GIGI CACING PADA ALAT PEMBENTUK MOTIF PADA KERAJINAN PLAT SENG - Suryawan, A. A. A.; Suweden, N.; Antara, I N. G.; Suputra, I G. N. O. (Buletin Udayana Mengabdi, 2016)
Craft industry center of trinkets ornaments made from zinc plates and other simillar materials in Bali province is developing quite rapidly. As household handicraft business, this business has been progressing types and forms in many variations. In the development of this business is experiencing problems such as decreased selling prices of production due to competition among craftsmen, high labor costs, and a lack of technical capacity and production innovation. For that needed guidance and help to increase production capacity and diminishes the cost of production. One of them by applying a usefull technology in the manufacture of the motif on the zinc plate. Making pattern requires the longest time in the production process, therefore it is necessary introduced a usefull technology that is a impact tool by implementing worm gear to create a motif in accordance with the desired shape. So, it would facilitate and accelerate the process, including by mothers who have aged. Based on the prototype that has been designed and constructed, the resulting pattern forming tool has been able to function properly. Although at the beginning of the operation by craftsperson are still slow, but with more frequent operate it they will be familiar, and pattern making will be faster and is expected to reduce the noise that occurs. IMPLEMENTASI RODA GIGI CACING PADA ALAT PEMBENTUK MOTIF PADA KERAJINAN PLAT SENG
Keywords: worm gear; impact tool; zinc plates craft; usefull technology